DESCRIPTION OF URINE SEDIMENT IN DIABETES MELITUS PATIENTS AT BUNDA THAMRIN HOSPITAL MEDAN IN 2023 - Rajagukguk, Tiara; Rajagukguk, Desy Lustiyani; Aritonang, Erlan (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Diabetes Mellitus (DM) is a group of chronic diseases caused by the pancreas being unable to produce the hormone insulin to meet the body's needs. This disease is characterized by an increase in blood glucose levels or hyperglycemia. Patients with diabetes mellitus are at risk of developing urinary tract infections due to immune factors, namely in the form of leukocyte disorders. High concentrations of sugar in the urine (glucoseuria) can inhibit leukocyte activity, in connection with that we need to look at the description of urine sediment in DM patients. The purpose of this study was to find out the results of examining the appearance of urine sediment in diabetes mellitus patients at Bunda Thamrin Hospital Medan in 2023. This type of research is descriptive analytic. The sample used is morning urine as much as 20 samples. Urine Sediment Examination Results in Patients with Diabetes Mellitus at Bunda Thamrin Hospital Medan in 2023 found that Erythrocytes increased entirely in 20 samples and Leukocytes obtained normal results in 12 samples (60%) and results increased by 7 samples (35%), then in epithelium found 12 samples (60%) normal and 8 samples (40%) increased, and in oxalate crystals found in 15 samples (75%) and 5 samples (25%) increased. It can be concluded that people with diabetes mellitus must maintain a healthy diet and exercise diligently, and always control blood sugar levels.